Woody species composition and diversity of agroforestry homegardens along altitudinal gradient in southwest Ethiopia - Tefera Jegora; Kitessa Hundera; Zerihun Kebebew; Adugna Eneyew (PLoS ONE, 2025)
Homegarden agroforestry systems that integrate trees with agricultural practices are usually valued for the conservation of farm biodiversity. Despite the system having a significant conservation role, litle is known on woody species composition and diversity following the elevation belt of southwest Ethiopia. A complete enumeration of 72 homegardens (24 each from altitudinal gradient) was purposively selected for woody species inventory. A total of 55 woody species belonging to 31 families and 45 genera were recorded. Of which, 56.4% of woody species are indigenous and two are endemic to Ethiopia. Family Fabaceae was the most represented family with eight species. The highest species richness (42) was observed at high altitudes followed by 39 species at middle and 31 species at low altitudes but no significant difference between them. Species richness significantly (P < 0.001) increased with increasing wealth status. The overall richness distribution was 46, 40, and 27 across rich, medium, and poor wealth classes respectively. Shannon diversity index differed significantly between poor and rich households. Pearson correlation result shows a strong positive and significant correlation between richness and wealth status. The mean woody species density was 89.06±9.25 and 1236.22±131.42 per garden and hectare, respectively. Stem density was significantly higher (P < 0.001) in wealthier farms. We found that, in southwestern Ethiopia wealthier agroforestry farms can support more woody species diversity in homegardens.